GOVERNANCE AND HUMAN RIGHTS IN SOUTH ASIA: AN EVOLVING PERSPECTIVE - Umadevi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
South Asia has been transitioning to more democratic forms of governance over the last two decades. Traditionally overlooked due to its deficiencies and poverty, the region is now witnessing significant economic and industrial growth. This paper explores the importance of good governance and human rights in South Asia, analyzing the unique challenges faced by these countries in reforming their governance and administrative systems. It also examines the emerging perspective of good governance in South Asia, which differs from Western concepts.